Two-Photon Optical Interrogation of Individual Dendritic Spines with Caged Dopamine - Araya, Roberto (2013)
We introduce a novel caged dopamine compound (RuBi-Dopa) based on ruthenium photochemistry. RuBi-Dopa has a high uncaging efficiency and can be released with visible (blue-green) and IR light in a two-photon regime. We combine two-photon photorelease of RuBi-Dopa with two-photon calcium imaging for an optical imaging and manipulation of dendritic spines in living brain slices, demonstrating that spines can express functional dopamine receptors. This novel compound allows mapping of functional dopamine receptors in living brain tissue with exquisite spatial resolution.